Introducing in-service English language teachers to data-driven learning for academic writing. (December 2019) - Chen, Meilin; Flowerdew, John; Anthony, Laurence
Abstract: Corpora are widely used in the creation of language learning and teaching materials, such as dictionaries, grammar books, textbooks, and vocabulary lists. Little work, however, has focused on how the DDL approach might be introduced successfully into a teacher training program. In this paper, we describe the background, implementation, and results of a DDL-focused teacher training workshop that is designed to introduce a corpus-assisted academic writing pedagogy to in-service English language educators in Hong Kong. To evaluate the success of the workshop and gain further insights on factors that might lead to instructors accepting or rejecting the approach, we administered a questionnaire to participants after the workshop and carried out a statistical analysis of the responses. Results revealed that participants generally had a positive experience of the training. Based on correlation tests, the results also showed that factors such as prior knowledge of corpora, prior experience in using corpora, motivation for professional development, and teaching experience, correlated significantly with teachers' perceptions of the difficulties in using corpus tools and an inclination to integrate data-driven learning in their future teaching. The findings may be related to broader research on teacher attitudes to the adoption of technology in the classroom.